2009
DOI: 10.1038/gt.2009.113
|View full text |Cite
|
Sign up to set email alerts
|

AAV9-mediated erythropoietin gene delivery into the brain protects nigral dopaminergic neurons in a rat model of Parkinson's disease

Abstract: We have recently shown that intrastriatal injection of recombinant human erythropoietin (EPO) protects dopaminergic (DA) neurons in the substantia nigra (SN) from 6-hydroxydopamine (6-OHDA) toxicity in a rat model of Parkinson's disease. However, systemic administration of EPO did not protect nigral DA neurons, suggesting that the blood-brain barrier limits the passage of EPO protein into the brain. In the present study, we used an adenoassociated viral (AAV) serotype 9 (AAV9) vector to deliver the human EPO g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 49 publications
0
37
1
Order By: Relevance
“…Recently, a single intravenous injection of AAV9 vectors expressing ␣-N-acetylglucosaminidase (NAGLU) in mice with mucopolysaccharidosis IIIB (MPS IIIB; lysosomal storage disease) led to correction of their lysosomal storage pathology in the central and peripheral nervous systems and correction of astrocytosis and neurodegeneration (25). Given these properties, AAV9 is currently under development for treatment of neurodegenerative diseases, such as spinal muscle atrophy, amyotrophic lateral sclerosis, Parkinson's disease, and MPS IIIB (7,25,29,30,45,80) (Table 1). Furthermore, while preexisting antibodies to AAVs have been shown to be detrimental to AAV gene delivery, the prevalence of antibodies to AAV9 is lower in humans than those of other serotypes, for example, AAV1 and AAV2 (8), making this serotype an even more attractive candidate for development as a gene delivery vector.…”
mentioning
confidence: 99%
“…Recently, a single intravenous injection of AAV9 vectors expressing ␣-N-acetylglucosaminidase (NAGLU) in mice with mucopolysaccharidosis IIIB (MPS IIIB; lysosomal storage disease) led to correction of their lysosomal storage pathology in the central and peripheral nervous systems and correction of astrocytosis and neurodegeneration (25). Given these properties, AAV9 is currently under development for treatment of neurodegenerative diseases, such as spinal muscle atrophy, amyotrophic lateral sclerosis, Parkinson's disease, and MPS IIIB (7,25,29,30,45,80) (Table 1). Furthermore, while preexisting antibodies to AAVs have been shown to be detrimental to AAV gene delivery, the prevalence of antibodies to AAV9 is lower in humans than those of other serotypes, for example, AAV1 and AAV2 (8), making this serotype an even more attractive candidate for development as a gene delivery vector.…”
mentioning
confidence: 99%
“…Intrastriatal but not systemic administration of EPO can reduce microglia activation in SN, protect nigral DA against 6-OHDA and improve neurobehavioral outcome in a rats [114]. In addition, adenoassociated viral serotype 9 (AAV9) vector mediated deliver of the human EPO gene into the brain of 6-OHDA-lesioned rats robustly promotes the expression of the human EPO gene in the striatum and the SN, prevents DA neuronal loss, attenuates the rotational and spontaneous forelimb use asymmetry ( Figure 2 and Table 2) [115].…”
Section: Parkinson's Diseasementioning
confidence: 91%
“…Halbert et al demonstrated the higher level and longer gene expression of both AAV2/5 and AAV2/9 compared with AAV2/2 in lung tissues (Halbert et al, 2001). In addition, AAV9 vector has been applied to the treatment of human disease models and recently has been suggested to be beneficial for liver and brain gene delivery (Chen et al, 2009;Xue et al, 2010).…”
Section: Discussionmentioning
confidence: 99%